(untitled) (Olhar de Professor, 2022)
This article is a state of the art regarding publications on mathematics and social media, particularly Facebook and Twitter, aiming at answering the questions: What do researchers in teaching and education say about the relationship between mathematics and social media? How are these social medias thought of in this context? In order to answer them, a survey and analysis of theses, dissertations and articles was carried out, on publications between 2012 and 2019, in the following databases: BDTD, CAPES, SCIELO, Google Scholar and CAPES Periódicos, The research identified two categories: social medias as ways of interaction and discussion; social medias as a study environment itself. The results showed that social medias are definitely learning environments, firstly informal but also as a formal tool of education, revealing a hybrid character depending on their usage.